Executive Function in Adolescence: Associations with Child and Family Risk Factors and Self-Regulation in Early Childhood - Berthelsen, Donna; Hayes, Nicole; White, Sonia L. J.; Williams, Kate E. (Frontiers in Psychology, 2017)
Executive functions are important higher-order cognitive skills for goal-directed thought and action. These capacities contribute to successful school achievement and lifelong wellbeing. The importance of executive functions to children’s education begins in early childhood and continues throughout development. This study explores contributions of child and family factors in early childhood to the development of executive function in adolescence. Analyses draw on data from the nationally-representative study, Growing up in Australia: The Longitudinal Study of Australian Children (LSAC). Participants are 4819 children in the Kindergarten Cohort who were recruited at age 4-5 years. Path analyses were employed to examine contributions of early childhood family factors, including family socio-economic position, parenting behaviors, maternal mental health, and a child behavioral risk index, to the development of executive function in adolescence. The influence of children’s early self-regulatory behaviors (attentional regulation at 4-5 years and approaches to learning at 6-7 years) were also taken into account. A composite score for the outcome measure of executive function was constructed from scores on three Cogstate computerized tasks for assessing cognition and measured visual attention, working memory, and spatial problem-solving. Covariates included child gender, age at assessment of executive function, Aboriginal and Torres Strait Islander status, speaking a language other than English at home, and child’s receptive vocabulary skills. There were significant indirect effects involving child and family risk factors measured at 4-5 years on executive function at age 14-15 years, mediated by measures of self-regulatory behavior. Child behavioral risk, family socio-economic position and parenting behaviors (anger, warmth, and consistency) were associated with attentional regulation at 4-5 years which, in turn, was significantly associated with approaches to learning at 6-7 years. Both attentional regulation and approaches to learning were directly associated with executive functioning at 14-15 years. These findings suggest that children’s early self-regulatory capacities are the basis for later development of executive function in adolescence when capabilities for planning and problem-solving are important to achieving educational goals.